Trained innate immunity as a potential link between preeclampsia and future cardiovascular disease - Carrasco-Wong, Ivo; Sanchez, Javiera M.; Gutierrez, Jaime A.; Chiarello, Delia I. (Frontiers in Endocrinology, 2024)
Preeclampsia (PE) is a complex pregnancy syndrome characterized by hypertension with or without proteinuria, affecting 2–6% of pregnancies globally. PE is characterized by excessive release of damage-associated molecular patterns (DAMPs) into the maternal circulation. This DAMP-rich milieu acts on innate immune cells, inducing a proinflammatory state characterized by elevated cytokines such as IL-1β and IL-18. This proinflammatory state in the mother and placenta results in the endothelial dysfunction strongly associated with cardiovascular disorders. While the immediate maternal and fetal risks of PE are well-documented, accumulating evidence indicates that PE also confers long-term cardiovascular risks to the mother, including hypertension, coronary heart disease, stroke, and heart failure. The underlying mechanisms connecting PE to these chronic cardiovascular conditions remain unclear. This article explores the potential role of trained innate immunity (TRIM) as a mechanistic link between PE and increased long-term cardiovascular risk. We propose that the persistent exposure to DAMPs during PE may epigenetically reprogram maternal innate immune cells and their progenitors, leading to TRIM. This reprogramming enhances the inflammatory response to subsequent stimuli, potentially contributing to endothelial dysfunction and chronic inflammation that predispose women to cardiovascular diseases later in life. Understanding the role of TRIM in PE could provide novel insights into the pathophysiology of PE-related cardiovascular complications and identify potential targets for therapeutic intervention. Further research is warranted to investigate the epigenetic and metabolic alterations in innate immune cells induced by PE and to determine how these changes may influence long-term maternal cardiovascular health.